Evaluation of mechanical and durability properties of concrete made with Indian bottom ash as replacement of fine aggregate - Ojha, P. N.; Trivedi, Amit; Singh, Brijesh; Singh, Abhishek (Journal of Asian Concrete Federation, 2020)
Bottom ash is a major by-product of the coal-based power generation process and it has particle size ranging from 45 μm to 150 μm. As per current provisions of IS: 383-2016, bottom ash can be used as replacement of natural fine aggregate up to 25% in case of lean concrete (less than M15 Grade) only. However, its use in reinforced and plain concrete is not permitted. Therefore, it is imperative to study the feasibility of using coal based bottom ash as a replacement of conventional fine aggregates (i.e., natural and crushed sand) in plain and reinforced concrete to increase the utilization of this industrial byproduct. In this study, natural and crushed sand were replaced with bottom ash at various percent-ages for prepa- ration of concrete and study its effect on fresh, hardened and durability properties of concrete. Bottom ash was collected from Vindhyachal thermal power plant of India. Experimental studies were conducted at w/c ratio of 0.65 and 0.40. Concrete mixes were studied and analyzed for various mechanical and durability properties. Based on fresh concrete properties i.e., workability, slump retention and strength development, it was observed that up to 50% replacement of conventional fine aggregate with bottom ash is technically feasible.